Fiction reading has a small positive impact on social cognition: A meta-analysis - Dodell-Feder, David; Tamir, Diana I (Journal of experimental psychology. General, 2018)
Scholars from both the social sciences and the humanities have credited fiction reading with a range of positive real-world social effects. Research in psychology has suggested that readers may make good citizens because fiction reading is associated with better social cognition. But does fiction reading causally improve social cognition? Here, we meta-analyze extant published and unpublished experimental data to address this question. Multilevel random-effects meta-analysis of 53 effect sizes from 14 studies demonstrated that it does: compared to nonfiction reading and no reading, fiction reading leads to a small, statistically significant improvement in social-cognitive performance (g = .15-.16). This effect is robust across sensitivity analyses and does not appear to be the result of publication bias. We recommend that in future work, researchers use more robust reading manipulations, assess whether the effects transfer to improved real-world social functioning, and investigate mechanisms. (PsycINFO Database Record (c) 2018 APA, all rights reserved).